Customer satisfaction towards Tenaga Nasional Berhad (TNB) services in Seri Iskandar / Mohammad Fauzi Mat Daud, Normalina Mahamud and Siti Shakina Sabri - Mat Daud, Mohammad Fauzi; Mahamud, Normalina; Sabri, Siti Shakina (2009)
The purpose of this study was to detennine levels of customer satisfaction at TNB Seri Iskandar. This study also attempts to help TNB Seri Iskandar to improve their services in order to satisfy their customers.In order to obtain information, a questionnaire was used the mam instrument. Other than that, information was obtained from primary and secondary data, an interview session with TNB Seri Iskandar Customer Services Manager and through observations. The questionnaire was tested for content validity by two different people in different organizations who checked for errors and ambiguity. In the context of face validity, Mr. Kammaruzaman, Customer Services Manager in TNB Seri lskandar and Puan Zurina Mahamood, Customer and Sale Assistance at Telekom Malaysia, Butterworth was asked to answer and determine the understanding. 250 questionnaires were distributed to residents in Taman Teknologi Seri Iskandar and Taman Maju. The return rate was 92.2%.Findings show the majority of respondents agreed that TNB Seri Iskandar met the standard as stated in their charter.It was reported that the majority of residents in Taman Teknologi Seri Iskandar and Taman Maju complained about electricity blackout, billing and natural disaster. The researchers also developed open ended questions to determine customer satisfaction towards TNB services. It can be concluded that the majority of residents in Taman Teknologi Seri lskandar and Taman Maju prefered to make no suggestion. This followed by (I) suggestion so that TNB Seri Iskandar must be honest and hardworking, (2) to improve their quality services, (3) patrol frequently (4) and improve their billings system.